The mental cost of job loss: assessing the impact on young adults in Vietnam - Freund, R; Favara, M; Porter, C; Scott, D; Thuc Duc, L (IZA Institute of Labor Economics, 2022)
We exploit the extensive job loss associated with the devastating fourth wave of COVID-19 in Vietnam to examine the impact of unemployment on young people's experiences of anxiety and depression. Using data from a longitudinal study with individual and survey-wave fixed effects, we show that job loss significantly increases levels of anxiety, but not depression. Specifically, job loss leads to a 5.9 percentage point increase in the probability of experiencing symptoms consistent with either mild or severe anxiety, almost doubling the pre-wave baseline. This effect is driven by individuals in the top earnings tercile who no longer live in their natal household - suggesting that the impact of job loss on anxiety is most acute among young people who are under pressure as the primary earners in their household. Perceived financial strain and food insecurity explain up to 22% of the estimated increase in anxiety. Our results support expanding mental health programmes to explicitly target young adults who have lost their job.